2011
DOI: 10.1186/1477-7525-9-7
|View full text |Cite
|
Sign up to set email alerts
|

Predialysis therapeutic care and health-related quality of life at dialysis onset (The pharmacoepidemiologic AVENIR study)

Abstract: BackgroundTo determine the impact of the quality of pre-dialysis nephrological care on health-related quality of life (HRQoL) at dialysis onset, which has not been well evaluated.MethodsAll adults who began a dialysis treatment in the administrative region of Lorraine (France) in 2005 or 2006, were enrolled in this prospective observational study.HRQoL was measured using the Kidney Disease Quality of Life V36 questionnaire, which enables calculation of two generic (physical and mental) and three specific dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
3
9
0
1
Order By: Relevance
“…Our study confirmed the results of the previous one that the chronic kidney disease severely hampers the quality of life. It also confirmed the results of other studies that the psychological well-being is affected worst (2). Some new evidence is added for the significant influence of the transplantation on the QoL.…”
Section: Results and Discussion Pharmacotherapy Costsupporting
confidence: 86%
“…Our study confirmed the results of the previous one that the chronic kidney disease severely hampers the quality of life. It also confirmed the results of other studies that the psychological well-being is affected worst (2). Some new evidence is added for the significant influence of the transplantation on the QoL.…”
Section: Results and Discussion Pharmacotherapy Costsupporting
confidence: 86%
“…The influence of the frequency and severity of symptoms on the perception of illness was also observed by other researchers [20,22]. The degree of this influence and attitudes towards the illness, in turn, are quite diverse.…”
Section: Discussionsupporting
confidence: 67%
“…Other researchers report [19][20][21] that ESRD patients undergoing renal replacement therapy experience many physical and emotional symptoms, which were evaluated in the present study with the use of the ESAS scale. It was noticed that physical symptoms of the disease, with the exception of chronic fatigue and dyspnoea, were not significantly severe and in terms of frequency they were similar to those of other researchers [19,21].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, some studies have shown that quality of life (QOL), assessed by internationally validated questionnaires, is worse in individuals with CKD compared to those without renal disease [ 10 ], and that the morbidity and mortality in end-stage disease are influenced by timing and quality care before the start of dialysis [ 8 , 11 ]. A systematic review of the QOL scores of these patients as a parameter of treatment adequacy is recommended [ 1 ] and it is also suggested that interventions in pre-dialysis are useful and can influence the clinical evolution in the later stages of the disease [ 1 , 8 ].…”
Section: Introductionmentioning
confidence: 99%